2023
DOI: 10.3390/nu15184041
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Determinants of Growth and Weight Gain in the Human Fetus and Preterm Infant

Laura Page,
Noelle Younge,
Michael Freemark

Abstract: The factors controlling linear growth and weight gain in the human fetus and newborn infant are poorly understood. We review here the changes in linear growth, weight gain, lean body mass, and fat mass during mid- and late gestation and the early postnatal period in the context of changes in the secretion and action of maternal, placental, fetal, and neonatal hormones, growth factors, and adipocytokines. We assess the effects of hormonal determinants on placental nutrient delivery and the impact of preterm del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 375 publications
0
3
0
3
Order By: Relevance
“…EGWG seems to correlate with cord blood hormone levels, which may be one of the determinants of a child’s later health [ 82 ]. Various cohort studies showed that GWG above recommendations increases the probability of cord hyperleptinemia [ 83 , 84 , 85 ].…”
Section: Fetal Programming For Metabolic Diseases In Children Born To...mentioning
confidence: 99%
“…EGWG seems to correlate with cord blood hormone levels, which may be one of the determinants of a child’s later health [ 82 ]. Various cohort studies showed that GWG above recommendations increases the probability of cord hyperleptinemia [ 83 , 84 , 85 ].…”
Section: Fetal Programming For Metabolic Diseases In Children Born To...mentioning
confidence: 99%
“…Pada tahun 2021 kembali turun menjadi 1,8% dengan jumlah absolut 295 orang dari 16.282 jumlah bayi baru lahir. 10,11 Berdasarkan uraian diatas dapat diketahui bahwa adanya peningkatan kejadian BBLR setiap tahunnya, serta menjadi salah satu prediktor tertinggi terhadap kematian bayi, sehingga membuat penulis tertarik untuk melakukan penelitian mengenai karakteristik bayi BBLR di RSI Siti Rahmah Padang periode 2019-2022.…”
Section: Pendahuluanunclassified
“…Ini berarti bahwa jika organ vital pada trimester pertama tidak terbentuk dengan sempurna atau mengalami kekurangan nutrisi, maka bayi yang dilahirkan akan tidak sempurna, prematur, dan BBLR. 11,14 Pada penelitian ini didapatkan hasil bahwa ibu yang melahirkan BBLR lebih banyak pada usia kehamilan ≥ 37 minggu (aterm) yaitu sebesar 57.1% sehingga tidak sesuai dengan teori yang ada bahwa resiko BBLR didapatkan dari ibu yang melahirkan < 37 minggu (preterm) karena semakin bertambahnya usia kehamilan seharusnya berat badan bayi semakin bertambah, tetapi ada penelitian yang menemukan bahwa ibu yang melahirkan bayi dengan BBLR terjadi pada usia kehamilan aterm. 4,15 Perbedaan hasil penelitian ini dengan teori bisa diakibatkan oleh beberapa faktor, salah satunya adalah kecukupan nutrisi ibu saat hamil.…”
Section: Penelitianunclassified
See 1 more Smart Citation
“…Milk leptin, adiponectin, ghrelin, resistin, and insulin-like growth factor-I (IGF-I) are appetite-regulating molecules involved in food intake regulation and energy balance in offspring [47][48][49][50][51]. Moreover, leptin, adiponectin, ghrelin, and resistin are involved in an infant's growth trajectory [52][53][54][55][56]. The details concerning molecular processes by which maternal milk adipokines contribute to the growth and health of the neonates need to be clarified [57,58].…”
Section: Introductionmentioning
confidence: 99%